Bioinspired Polyethersulfone Membrane Design via Blending with Functional Polyurethane - Mei Han; Qiang Liu; Baihai Su; Shudong Sun; Changsheng Zhao (International Journal of Polymer Science)
Polyurethanes (PUs) are currently considered to be biocompatible materials but limited by a low resistance to thrombus. We therefore design a heparin-like PU (HLPU) to modify polyethersulfone (PES) membranes approaching integrated antifouling and antithrombotic properties by bioinspiration of heparin structure. Poly(vinyl pyrrolidone)-HLPU (PVP-HLPU) was synthesized via reversible addition-fragmentation chain transfer polymerization of VP using PU as a macroinitiator and then sulfonated by concentrated H2SO4. FTIR and NMR results demonstrated the successful synthesis of PVP-HLPU. By incorporation of PVP-HLPU, the cross-sectional structure of PES composite membranes altered from finger-like structure to sponge-like structure resulting in tunable permeability. The increased hydrophilicity verified by water contact angles benefited both the permeability and antifouling property. As a consequence, the composite membranes showed good blood compatibility, including decreased protein adsorption, suppressed platelet adhesion, lowered thrombin-antithrombin III generation, reduced complement activation, and prolonged clotting times. Interestingly, the PVP-capped HLPU showed better blood compatibility compared to polyethyleneglycol-capped and citric acid-capped HLPUs. The results demonstrated the enhanced antifouling and antithrombotic properties of PES hemodialysis membranes by the introduction of functional HLPUs. Also, the proposed method may forward the fabrication of hemocompatible membranes via bioinspired surface design.